Congenital Syphilis in Ecuador is a still unsolved problem? - Fabricio González-Andrade; Gabriela Aguinaga Romero; Yenddy Carrero; Carolina Ocaña (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2021)
Congenital syphilis represents a public health problem. Despite the increases in prenatal care coverage, the actions implemented still show low effectiveness in their prevention. An epidemiological, observational, cross-sectional study is presented, in which data were obtained from the National Institute of Statistics and Censuses (INEC) with the purpose of establishing the current situation of congenital syphilis in Ecuador, taking into consideration the data throughout the last years. According to the registries, no cases of late syphilis have been reported for 6 years. The reports prior to 2004 are irregular, the data recorded from 2005 on are more reliable due to the mean and standard deviation data. There is a slight downward trend from 2003 to 2011 showing an increase of 200 reported cases in 2013. No detailed data was found as of 2016. Congenital syphilis still prevails, with a slightly higher prevalence in men, although the ratio (male / female) is kept at 1: 1. Since 2005 there is no significant variation. A downward slope is evident, but the mean values would indicate a plateau during the last 7 years. This fact will determine a blockage of the expected decrease in the number of cases. There is no proper official